2012
DOI: 10.3758/s13421-012-0192-6
|View full text |Cite
|
Sign up to set email alerts
|

From maps to navigation: The role of cues in finding locations in a virtual environment

Abstract: In two experiments, participants navigated through a large arena within a virtual environment (VE) to a location encoded in memory from a map. In both experiments, participants recalled locations by navigating through the VE, but in Experiment 2, they additionally recalled the locations on the original map. Two cues were located outside and above the walls of the arena at either north-south locations or east-west locations. The pattern of angular bias was used to infer how the cues affected the creation of spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Thus, the cue–geometry association was required for reorientation after each rotation to different test headings. The cue–geometry association also provides an explanation for the results of Hutcheson and Wedell ( 2012 ), in which distal cues served as boundaries in a virtual environment (VE). One target and two external cues (north and south or east and west) were studied in a map on a computer screen.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, the cue–geometry association was required for reorientation after each rotation to different test headings. The cue–geometry association also provides an explanation for the results of Hutcheson and Wedell ( 2012 ), in which distal cues served as boundaries in a virtual environment (VE). One target and two external cues (north and south or east and west) were studied in a map on a computer screen.…”
Section: Discussionmentioning
confidence: 89%
“…Even without awareness of the starting location and the absence of maps, the individual can successfully complete the task based on the advice given to them and their own observations of the environment. The use of these visual cues or abstract representations in navigation rather than explicit directions based on distance was observed by Hutcheson et al in [5], indicating an underlying cognitive process supported by advice-giving that enables the goal to be achieved. In this paradigm, advice-giving may be used to explain the dominance of mental rotation higher up the primate evolutionary ladder.…”
Section: Introductionmentioning
confidence: 96%
“…Hutcheson and Wedell [11] discuss how, when humans are immersed in an environment and navigating to a certain location, they tend to use these qualitative, abstract representations to navigate as opposed to using more precise distances or explicit directions; Menzel et al [4] observed a similar tactic with a nonhuman primate. The Bonobo being observed had to travel from a start location to a designated goal; it did not take a rigid trajectory but varied its path [4].…”
Section: Related Workmentioning
confidence: 99%